2014
DOI: 10.5897/ajar12.1741
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the laser leveled land leveling technology on crop yield and water use productivity in Western Uttar Pradesh

Abstract: A study has been conducted for 3 year on impacts of the laser land leveling versus traditional land leveling on water use productivity and crop yields. The major concerns were effectiveness of laser land leveling as a water saving tool in the new context of land use and ownership, affordability of laser land leveling for farmers and the economic viability of this technology. These research questions were studied in a sizable area of laser leveled and neighboring non-leveled (control) fields for 2009 to 2011. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…This implies that changes in cropping pattern, planting dates, adoption of new agricultural and water saving technologies have significant impact on agricultural productivity and farm income [16,23,24,[29][30][31][32]. Similarly, many empirical studies from developed and developing countries shows that applications of CSA practices and technologies increased crop yield, resource use efficiency, net farm income, and reduced greenhouse gas emissions [24,[33][34][35][36][37][38][39][40][41]. Additionally, a few studies from Pakistan found that implementation of new agricultural practices and technologies, and adaptation to climate change significantly influencing the agricultural productivity, farm income and resource use efficiency [12,15,16,32,[42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…This implies that changes in cropping pattern, planting dates, adoption of new agricultural and water saving technologies have significant impact on agricultural productivity and farm income [16,23,24,[29][30][31][32]. Similarly, many empirical studies from developed and developing countries shows that applications of CSA practices and technologies increased crop yield, resource use efficiency, net farm income, and reduced greenhouse gas emissions [24,[33][34][35][36][37][38][39][40][41]. Additionally, a few studies from Pakistan found that implementation of new agricultural practices and technologies, and adaptation to climate change significantly influencing the agricultural productivity, farm income and resource use efficiency [12,15,16,32,[42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…Almost all the farmers surveyed are aware of laser land levelling, and more than 83% have adopted it (Table 8), because of the yield advantage from levelling, which may not be the case for other options (Naresh et al 2014;Jabran et al 2015;Ullah and Datta 2018). But, despite considerable awareness, the adoption and use of the other technologies and practices is poor: about 17% of the farmers surveyed adopted raised bed cultivation, less than 5% adopted the other technologies and practices, and the adoption of drip irrigation was negligible.…”
Section: Awareness Adoption and Capacity-building Needs For Sustainab...mentioning
confidence: 99%
“…Laser land leveling saves farm inputs like water and fertilizers, improves crop stand (El-Behery and El-Khatib, 2001). The use of laser land leveling increases yields and saves irrigation water as compared to traditional method of leveling in different cropping systems (Naresh et al, 2014).…”
Section: Introductionmentioning
confidence: 99%